# Not following algebra in a proof, can anyone please explain it?

So I'm learning mathematical induction as a proof technique (teaching myself discrete math as a foundation for a comp sci class I'm going to be taking). My algebra is a little rusty, and I cannot follow how this proof gets to the second step of (1/4)k^2(k+1)^2+(k+1)^3. I'm also lost on how we get from line 2 to 3, where it goes from (1/4)K^2(k+1)^2 + (K+1)^3 to (1/4)(k+1)^2[k^2+4(k+1)]. Any help is appreciated!

-
It just distributes the square $\bigg[ \frac{k(k+1)}{2}\bigg]^2 = \frac{k^2(k+1)^2}{2^2}$. – Robert Cardona Jan 26 '13 at 6:52
In general, $\left(\frac{a}{b}\right)^2=\frac{a^2}{b^2}$. More generally still, $\frac{a}{b}\cdot\frac{c}{d}=\frac{ac}{bd}$. – André Nicolas Jan 26 '13 at 6:53
Ah, cool. How does the 1/4 then get factored out? – user56763 Jan 26 '13 at 7:00
$(\frac {1}{2} )^2 = \frac {1}{4}$. – Calvin Lin Jan 26 '13 at 7:00
Bingo, thanks. I forgot that (a/b)c = ac/b – user56763 Jan 26 '13 at 7:17

Now L.H.S. is \begin{align} 1^3+2^3+\dots+k^3+(k+1)^3 &=\left[\frac{k(k+1)}{2}\right]^2+(k+1)^3\\ &=\frac14k^2(k+1)^2+(k+1)^3\\ &=\frac14\color{#C00000}{k^2}(k+1)^2+\frac14(k+1)^2\color{#00A000}{4(k+1)}\\ &=\frac14(k+1)^2\left[\color{#C00000}{k^2}+\color{#00A000}{4(k+1)}\right]\\ &=\frac14(k+1)^2\left[k^2+4k+4\right]\\ &=\frac14(k+1)^2(k+2)^2\\ &=\left[\frac{(k+1)(k+2)}{2}\right]^2 \end{align} Therefore L.H.S.=R.H.S
i.e. $\displaystyle1^3+2^3+\dots+k^3+(k+1)^3=\left[\frac{(k+1)(k+2)}{2}\right]^2$